2012
DOI: 10.1371/journal.pone.0029251
|View full text |Cite
|
Sign up to set email alerts
|

Colour Patterns Do Not Diagnose Species: Quantitative Evaluation of a DNA Barcoded Cryptic Bumblebee Complex

Abstract: Cryptic diversity within bumblebees (Bombus) has the potential to undermine crucial conservation efforts designed to reverse the observed decline in many bumblebee species worldwide. Central to such efforts is the ability to correctly recognise and diagnose species. The B. lucorum complex (Bombus lucorum, B. cryptarum and B. magnus) comprises one of the most abundant and important group of wild plant and crop pollinators in northern Europe. Although the workers of these species are notoriously difficult to dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 51 publications
7
110
1
Order By: Relevance
“…Bertsch (2009) was able to assign all but three investigated queen specimens to the correct species with the above mentioned characters, according to the biochemical evidence (n = 28). In contrast, using a larger sample from the British Isles and Denmark (n = 67), Carolan et al (2012) showed that especially the collar-characters are not reliable for species diagnosis since they show overlap (see Fig. 4: doi: 10.1371/journal.pone.0029251.…”
Section: Identification Of Queensmentioning
confidence: 92%
See 2 more Smart Citations
“…Bertsch (2009) was able to assign all but three investigated queen specimens to the correct species with the above mentioned characters, according to the biochemical evidence (n = 28). In contrast, using a larger sample from the British Isles and Denmark (n = 67), Carolan et al (2012) showed that especially the collar-characters are not reliable for species diagnosis since they show overlap (see Fig. 4: doi: 10.1371/journal.pone.0029251.…”
Section: Identification Of Queensmentioning
confidence: 92%
“…The interspecific genetic divergences of the species are considerably larger than the intraspecific divergences and these patterns are stable over wide geographic ranges of Europe. In measureable terms, the genetic divergences between the species, based on the Kimura 2-parameter model of DNA sequence evolution (Kimura 1980), from Carolan et al (2012) ranged from 0.033 to 0.044, whereas intraspecific distance was from 0.002 to 0.004. In the analysis by Murray et al (2008), which was based on Tamura-Nei (Tamura and Nei 1993), the distances are slightly smaller.…”
Section: Nucleotide Sequence Data Improved Our Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their high morphological similarity, individuals of B. terrestris, B. lucorum, B. cryptarum, and B. magnus were pooled into one operational taxonomic unit (OTU), B. terrestris s.l. (Carolan et al 2012;PrysJones and Corbet 2011). After the worker bees were immobilized in a marking cage with a soft plunger, the two pollen loads were gently removed using a toothpick.…”
Section: Pollen Loads For Constancy Estimatesmentioning
confidence: 99%
“…DNA barcoding may be used to tackle very different issues: controlling the identity of food of animal and/or vegetal origin, e.g. fishes for sale in supermarkets (Rasmussen et al, 2009), identifying immature specimens and resolving adult and larval stages within the same species (Hebert et al, 2004a;Paquin and Hedin, 2004;Greenstone et al, 2005;Hubert et al, 2010), studying extinct species (Lambert et al, 2005) and discriminating possible cryptic species (Hebert et al, 2004a(Hebert et al, , 2004bHogg and Hebert, 2004;Barrett and Hebert, 2005;Ward et al, 2005;Lara et al, 2010;Carolan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%